Thyroglossal cysts and fistulae (Bangladesh Journal of Otorhinolaryngology, 2011)
Objective: This study aimed to observe the different diagnostic approaches and differential diagnosis of 20 cases of thyroglossal cysts and fistulas managed surgically. Methods: The medical records of patients treated for thyroglossal cysts in the department of Ear, Nose, Throat Surgery at regional hospital of CMH Dhaka, Comilla, Rangpur and Ibn Sina Medical College and Hospital Dhaka, from 2002 to 2009 were reviewed. History and examination reports were studied. Their medical records were reviewed for clinical presentations, investigations, operative findings, histopathology and treatment outcome. After a clinical diagnosis, they had individualized investigations (USG, MRI, radio iodine scan, FNAC etc) prior to the Sistrunk’s operation. This was a retrospective study. Results: In this study the site of presentation of thyroglossal duct cysts were 15% suprahyoid, 80% thyrohyoid and 5% supra sternal. Present study revealed that 95% swelling were in the midline. 50% of the study cases of swellings were 1-2 cm, 60% swellings were soft and cystic moved with swallowing, 30% were firm but mobile. Skin was free in 80% cases and 20% had sinuses. 60% cysts contained fibrous tissue and 30% cysts contained thyroid tissue. At an average follow up of 2 years, all are asymptomatic and well. Conclusion: Although the clinical and histological presentations of these 20 cases are not rare, they do illustrate how varied thyroglossal cyst can be with respect to patient age, anatomic site or associated sign and symptoms. Key Words: Thyroglossal cyst; Sistrunk’s operation. DOI: 10.3329/bjo.v17i1.7629 Bangladesh J Otorhinolaryngol 2011; 17(1): 53-58